Tanggung Jawab Hukum Perusahaan terhadap Pencemaran Lingkungan dalam Industri Pertambangan Berdasarkan Undang-Undang No. 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup: (Studi Kasus PT Gema Kreasi Perdana di Pulau Wawonii) - Elvira Fitriyani Pakpahan; Marsa Suhaila (CV Rewang Rencang, 2025)
The urgency of the issue of environmental pollution caused by the mining industry in Indonesia is increasing, especially with the rise of mining activities that do not pay attention to sustainability aspects. The case of PT Gema Kreasi Perdana (GKP) on Wawonii Island, Southeast Sulawesi, is a concrete example of how mining activities can have significant ecological, social and legal impacts. This research aims to analyze the form of corporate legal liability for environmental pollution based on Law Number 32 of 2009 concerning Environmental Protection and Management (UU PPLH). This research uses descriptive qualitative method with normative juridical approach and case study. The results show that PT GKP can be subject to legal liability based on the principle of strict liability without the need to prove the element of fault. The company was also proven to have violated licensing regulations and community rights, which had a direct impact on the environment and community welfare. The conclusion of this study indicates that enforcement of environmental legal liability must be supported by a strong regulatory system and strict supervision. This study recommends periodic evaluation of mining licenses and ecological restoration as absolute requirements for the sustainability of the mining industry in Indonesia.